Properties and Applications of a New Chemical Grouting Material - Xiaohua Yang; Kunlong Zheng; Lixiao Xu; Nieyangzi Liu (Advances in Civil Engineering)
The study investigates a new chemical grout by mixing the main agent, auxiliary agent, catalyst, foam stabilizer, solvent, and water, to treat the distress of railway tunnel. The orthogonal design was used to obtain 16 groups of grout proportion schemes, and reasonable proportion parameters were screened using laboratory and field tests. Additionally, this study included detailed research on the grout performance. The test results showed that the proportion schemes of groups 3, 4, and 15 grout were the most reasonable. In particular, for group 3, the viscosity is 663 MPa·s, the curing time is 119 s, the foaming capacity is 1589%, and the compressive strength is 20.16 MPa. For group 4, the viscosity is 663 MPa·s, the curing time is 137 s, the foaming capacity is 1809%, and the compressive strength is 17.76 MPa. For group 15, the viscosity is 281 MPa·s, the curing time is 98 s, the foaming capacity is 1173%, and the compressive strength is 26.79 MPa. Groups 4 and 15 grouts were used to treat the frost boiling and track bed subsidence in existed railway tunnels. Based on this, field monitoring showed that muddy water became clear water with an average depth of only 4 mm in the drainage ditch and that the irregular subsidence of the track bed was also solved after treatment. According to the aforementioned experimental research and analysis, it is proven that new grout not only exhibits a reasonable solidification time, high strength, and excellent waterproofing and impermeability with no pollution of the environment but also can be produced by a safe and convenient synthesis method. Group 4 is suitable for treating tunnel seepage, group 15 is suitable for structural reinforcement, and group 3 confers the advantages of seepage prevention, leakage stoppage, and reinforcement.